Implementasi Penilaian Kurikulum 2013 SDN Sukasari Kota Tangerang - Ina Magdalena; Dias Julianti Agustin; Gerdah Cita Dilla; Khairunnisa Khairunnisa (Jurnal Halaqah, 2020)
The development of curriculum in Indonesia, certainly involves a lot of aspects, like the development of lessons, method and media used, and also development in the assessment. For 2013 Curriculum, assessment becomes difficult to part, because in assessment involve a lot of aspect and time just for assessing children. Because involving cognitive, affective and psychomotor in children that make teachers difficult for doing the assessment. So that teachers must have a strategy and methods for doing the assessment. With no exception in SDN Sukasari 5 Tangerang city, teacher little by little doing assessment until the column of assessment children full. We get some data from doing an interview with a teacher. For this time has available application for upload score, daily score although report book for easy teacher for assessment.